NEW FINDINGS ON BOSTRICHUS CAPUCINUS LINNAEUS, 1758 (COLEOPTERA: BOSTRICHIDAE) IN TURKEY - Ozgen, Inane (Parlar Scientific Publications (P S P), 2018)
Bostrichus capucinus (Linnaeus, 1758) (Coleoptera: Bostrichidae) is a xyllofag species that causes secondary damage in various culture plants in European countries and in Turkey. The damages caused by this species on the fig plant in Turkey and mode of damage are published for the first time with this study. Dimensions of the pupa nest of the species are also given. Furthermore; the species Dendrosotinus ferrugineus (Marshall, 1888) (Hymenoptera: Braconidae) as the new larva parasitoid of B. capucinus has been determined in this study. This is the first record that this species parasitizes the subspecies belonging to the Bostrychidae family. This species emerges from the cocoons of B. capucinus in the xylemic galleries. Moreover; both species have been determined in the fauna of Southeastern Anatolian Region and in Diyarbakir Province for the first time.
Keywords: Bostrichus capucinus; Dendrosotinus ferrugineus; new host; new record parasitoid; Ficus caria; Turkey